2014
DOI: 10.1177/1524839914553300
|View full text |Cite
|
Sign up to set email alerts
|

Dogs, Physical Activity, and Walking (Dogs PAW)

Abstract: Preliminary results suggest that this pilot intervention is an acceptable and feasible strategy for promoting dog walking among dog owners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…We have previously reported on the feasibility, acceptability, and immediate outcomes of the Dogs PAW postintervention (Richards, Ogata, & Ting, 2015). In this preliminary analysis, participants agreed that the intervention e-mails were easy to read and understand and that the frequency of e-mails was adequate.…”
Section: Purposementioning
confidence: 92%
See 2 more Smart Citations
“…We have previously reported on the feasibility, acceptability, and immediate outcomes of the Dogs PAW postintervention (Richards, Ogata, & Ting, 2015). In this preliminary analysis, participants agreed that the intervention e-mails were easy to read and understand and that the frequency of e-mails was adequate.…”
Section: Purposementioning
confidence: 92%
“…Dogs PAW was a 3-month, e-mail-based RCT designed to increase dog walking among dog owners (see Richards et al, 2015, for a complete description). Briefly, Dogs PAW was developed to be in line with SCT and based off the individual, interpersonal, and environmental correlates of dog walking found in two previous studies (Rhodes et al, 2012;Richards et al, 2013b).…”
Section: Intervention Procedures and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, most of the 29 studies in this systematic review were cross-sectional associations between dog ownership and walking or physical activity levels [5]. The magnitude of this effect was replicated in small-scale dog walking intervention trials [6,7]. However, some studies found the absolute difference in reported walking or physical activity between dog owners and non-dog owners to be small in magnitude or non-significant [810].…”
Section: Introductionmentioning
confidence: 93%
“…The Scopus data base was used from 2000 to the end of 2016, and all papers with the Title terms (dog* AND (physical activity) or walk*)) were included. Two raters (SK and AB) considered all abstracts and coded them as [1] correlates or prevalence studies using cross sectional designs [including the association between dog walking and physical activity]; [2] editorials, opinion pieces; [3] measurement studies; [4] qualitative research; [5] interventions to increase DW; [6] epidemiological studies, longitudinal, cohorts, and [7] health benefits of pets, dogs. Inter-rater agreement was 87%, and all discrepancies were reconciled.…”
Section: Introductionmentioning
confidence: 99%